PENGARUH KOMPENSASI MANAJEMEN, KEPEMILIKAN INSTITUSIONAL, DAN REPUTASI AUDITOR TERHADAP MANAJEMEN PAJAK PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Nasir, Azwir; Ilham, Elfi; ', Khairunnisa R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of management compesation, institutional ownership and auditor reputation on the tax management. Independent variables used in this study are management compesation, institutional ownership and auditor auditor reputation, while the dependent variable in this study is tax management are measured using Effective Tax Rate (ETR). Populations used in this study is manufacture companies listed on IDX 2011-2013 where the total population is used by 19 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 57 (19x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables management compesation, institutional ownership, and auditor reputation which has a significant influence on tax management.Keywords : Management Compesation, Institutional Ownership, Auditor Reputation, Tax Management, and Effective Tax Rate